Key Components and Design Strategy for a Proton Exchange Membrane Water Electrolyzer - Yuhao Chen; Chaofan Liu; Jingcheng Xu; Chengfeng Xia; Ping Wang; Bao Yu Xia; Ya Yan; Xianying Wang (Small Structures, 2023)
As the most attractive energy carrier, hydrogen production through electrochemical water splitting (EWS) is promising for resolving the serious environmental problems derived from the rapid consumption of fossil fuels globally. The proton exchange membrane water electrolyzer (PEMWE) is one of the most promising EWS technologies and has achieved great advancements. To offer a timely reference for the progress of the PEMWE system, the latest advancements and developments of PEMWE technology are systematically reviewed. The key components, including the electrocatalysts, PEM, and porous transport layer (PTL) as well as bipolar plate (BPP), are first introduced and discussed, followed by the membrane electrode assembly and cell design. The highlights are put on the design of the electrocatalyst and the relationship of each component on the performance of the PEMWE. Moreover, the current challenges and future perspectives for the development of PEMWE are also discussed. There is a hope that this review can provide a timely reference for future directions in PEMWE challenges and perspectives.